Chemical analysis of the degradation of acid orange 52 using advanced oxidation technologies - Jaramillo Sierra, Bethsabet; Díaz Martínez , Alexander; Mercado Cabrera, Antonio; Ibañez Olvera, Mario (JOURNAL OF BASIC SCIENCES, 2024)
The degradation of the acid orange 52 (AN) dye was carried out applying different Advanced Technologies, a cylindrical configuration recirculation reactor were used, the initial concentration of AN is 20 mg/L in 400 mL of solution, the treatment time consisted of 60 minutes, taking samples every 10 minutes and analyzing it by UV-vis spectrometry. The effect of the oxidizing agents used in individual and synergistic systems, the treatment time, the final pH, the generation of CO2 and the change in the coloration of the samples were determined. Efficiencies of up to 99% were obtained when using the O3/1 mL H2O2/UV method and 60 minutes, the final pH was 2.9 attributed to the generation of by-products, 35 mg/L of CO2 were obtained at the end of the process indicating that a percentage of mineralization was reached, finally a 100% decrease in color were observed.
Keywords: Ultraviolet Radiation; Ozone; Hydrogen Peroxide; Carbon Dioxide; Pollution